2012
DOI: 10.2298/tsci110708011k
|View full text |Cite
|
Sign up to set email alerts
|

Biomass gasification with preheated air: Energy and exergy analysis

Abstract: Due to the irreversibilities that occur during biomass gasification, gasifiers are usually the least efficient units in the systems for production of heat, electricity, or other biofuels. Internal thermal energy exchange is responsible for a part of these irreversibilities and can be reduced by the use of preheated air as a gasifying medium. The focus of the paper is biomass gasification in the whole range of gasification temperatures by the use of air preheated with product gas sensible heat. The energe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Karamarkovic et al [ 6 ] have found that the preheating of gasifying air by heat exchanging with the product gas is beneficial for the energetic and exergetic efficiencies of the gasification process. The higher the preheating temperature the larger their efficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…Karamarkovic et al [ 6 ] have found that the preheating of gasifying air by heat exchanging with the product gas is beneficial for the energetic and exergetic efficiencies of the gasification process. The higher the preheating temperature the larger their efficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…The discussed paper [1] is only an attempt toward a positive discussion toward increasing the amount of available information from the second law of thermodynamics. The only objective is to analyze the delivered information and intrinsic limits [12] of both the first law analysis (Gibbs free energy) and the second law analysis (exergy or entropy generation).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Hence, numerous models were proposed to describe the gasification unit . Energetic and exergetic analyses were also carried out to optimize the gasifier design and operating parameters depending on biomass type and final syngas use. …”
Section: Introductionmentioning
confidence: 99%